GRAMMAR RANGE IN ENGLISH (Web of Teachers: Inderscience Research, 2024)
In this article, you will get acquainted with the most relevant topic of grammar range.In grammatical range: Being able to use a variety of sentence structures, tenses, and other items to convey intended meaning.It is significant in speech.